Geriatrics and Ageing in the Soviet Union : Medical, Political and Social Contexts - Grant, Susan 1988- HerausgeberIn; Scarborough, Isaac HerausgeberIn (Bloomsbury Academic, 2023)
This open access book brings together an eclectic cast of scholars in related disciplines to examine ageing in the Soviet Union, covering the practice of geriatrics, the science of gerontology, and the experience of growing old. Chapters in the book focus on concepts and themes that analyse Soviet ageing in its medical, political and social contexts, both in the Soviet Union and internationally. Ageing was hardly a uniquely Soviet phenomenon: over the past fifty years, moreover, governments and societies have been dealing with steady increases in their ageing populations. Almost paradoxically, however, societal focus on this ageing population, its lives, and its social impact remains extremely limited. Compared to most sciences, gerontology is pitifully underfunded; geriatrics is amongst the least prestigious branches of medicine; and while the world’s population is growing undeniably older, great disagreement remains over what can and should be done in response. These were the same challenges that the USSR faced in the post-war decades (1945-1991), and the contributions included in this volume help to flesh out and contextualize the example of Soviet gerontology and geriatrics as one possible model of response. Geriatrics and Ageing in the Soviet Union captures the growing interest in this important subject, demonstrating the influence of ageing on Soviet science and society and the impact of Soviet gerontology and geriatrics at a global level. The book is available under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com. Open access was funded by the Wellcome Trust and Liverpool John Moores University